Information seeking by orangutans: a generalized search strategy? - Marsh, Heidi L.; MacDonald, Suzanne E. (Animal cognition, 2012)
Recent empirical work has suggested that some species of non-human primates may be aware of their knowledge states. One finding to support this claim is that they seek information about the location of a hidden food item when they are unsure of its location, but not when they already know where it is, which purportedly demonstrates metacognition. However, this behaviour may instead reflect a generalized search strategy, in which subjects reach for food when they see it, and search for it when they do not. In this experiment, this possibility was addressed by testing orangutans in three conditions in which the location of a food item was sometimes known to subjects, and other times required subjects to visually seek the missing information. All subjects exhibited behaviour consistent with a metacognitive interpretation in at least two of the three conditions. Critically, in two of the conditions, subjects refrained from seeking visual information, and correctly found the hidden food item without ever seeing it, using inference by exclusion. The results suggest that animals that succeed in this information-seeking task are not merely acting according to a generalized search strategy, and instead seek information adaptively according to their knowledge states.